Isolasi dan Identifikasi Senyawa Metabolit Sekunder Ekstrak Daun Kopi Arabika (Coffea arabica) Menggunakan Teknik Kromatografi - Nurul Amaliya Hikma; A. Nur Afiah Rahman; Siti Aisyah Basir; A. Yeyen Maharani; Pingki Pingki; A. Putri Wulandari Syam; Mufidah Humairah S; Nur Andini; Fatma Fatma; Fityatun Usman (Inovasi Kesehatan Global, 2025)
This study aims to extract and purify secondary metabolite compounds from Coffea arabica leaves using various separation techniques, such as maceration, column chromatography, thin layer chromatography (KLT), and preparatory KLT, and followed by flavonoid content analysis using UV-Vis spectrophotometry. The process begins with drying the arabica coffee leaves, then extraction is carried out using 96% ethanol for three days. After that, the solvent is evaporated with a rotary evaporator at 60°C to obtain a viscous extract. The extracts were further separated using column chromatography with a mixed solvent of n-hexane: ethyl acetate (3:1), resulting in 12 fractions that showed color differences, which was an indication of the diversity of the compounds in the extract. Advanced identification was carried out with KLT using methanol solvents: chloroform (9:1) at UV wavelengths of 254 nm and 366 nm, indicating the presence of compounds with medium to high polarity. Furthermore, the isolated compounds were further separated using the preparative KLT (KLTP) method. To determine the flavonoid content, UV-Vis spectrophotometry was performed at a wavelength of 431 nm, using quercetin as standard. The results of the analysis showed that Arabica coffee leaf extract had a yield of 7.35% and a total flavonoid content of 19.0605 mgQE/g. These findings show that arabica coffee leaves are a source of flavonoid compounds that have the potential for the development of herbal or phytopharmaceutical products. The flavonoid content found may provide health benefits, particularly in increasing antioxidant activity, which can be used in the treatment of oxidative stress-related diseases. The results of this study also open up opportunities for the development of plant-based products, especially Arabica coffee, in the pharmaceutical and cosmetic industries as an efficacious natural active ingredient.